An Intercultural Management Perspective of Foreign Student’s Adaptation in Chinese Universities: A Case Study of China Three Gorges University - Ping, L.; Jing, X.; Othman, B.; Yuefei, F.; Kadir, Z. B. A.; Ping, X. (Engineering, Technology & Applied Science Research, 2019)
Globalization, the desire to access quality education and better opportunities abroad as well as the need to develop one’s capacities and many other factors have caused increased migration of international students and teachers into Chinese universities. China has recorded over a 67% increase in higher education enrolment between 2011 and 2017. This increased level of student migration in China has brought an unprecedented number of challenges especially in transitioning into the cultural settings in China. As a result, Chinese universities, in addition to their various obligations and roles in ensuring quality teaching and learning, have to engage in intercultural management to help foreigners’ transition seamlessly into the cultural landscape of China. This study examines intercultural adaptation of sojourners from an intercultural management perspective. Using a mixed method approach, specifically an explanatory mixed method design, a sample of 140 respondents was investigated regarding their cultural adaptation to a Chinese university. The positive and negative aspects of intercultural management as it relates to the university used in the case study were also explored. Findings from the study were discussed in depth and recommendations for a holistic intercultural management system were made.